THE IMPACT OF THE STEM LEARNING MODEL ON STUDENTS’ SCIENCE PROCESS SKILLS AND CRITICAL THINKING SKILLS IN PHYSICS EDUCATION - Putri Dewi (INERCYS: Institute of Educational, Research, and Community Service, 2026)
The development of science process skills and critical thinking skills is a crucial aspect of physics education, as these competencies are essential for preparing students to face the challenges of 21st-century learning and to solve scientific problems effectively. This issue highlights the need for further research on the effectiveness of implementing STEM-based learning models in enhancing students’ higher-order thinking skills. This study aims to analyze the effect of the STEM learning model on students’ science process skills and critical thinking skills in physics learning. The research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. Data were collected through tests and observation sheets designed to measure science process skills and critical thinking skills based on higher-order thinking indicators. The collected data were analyzed using descriptive statistics, independent samples t-test, and normalized gain (N-gain) analysis. The results indicate that the implementation of the STEM learning model significantly improves students’ science process skills and critical thinking skills, as evidenced by the differences in posttest mean scores between the experimental and control groups and N-gain values in the medium to high categories. These findings suggest that STEM-based learning is effective in fostering higher-order thinking skills. This study provides a significant contribution to the development of physics education at both national and international levels through the implementation of innovative, student-centered, and interdisciplinary learning models that support the development of 21st-century skills. Furthermore, the findings are expected to serve as a reference for future research, particularly in the development of STEM-based learning models and the enhancement of higher-order thinking skills, as well as to encourage more in-depth and applicable subsequent studies.